Casting a new light on the seismic risk assessment of stone masonry buildings located within historic centres. (June 2020) - Maio, Rui; Estêvão, João M.C.; Ferreira, Tiago M.; Vicente, Romeu
Abstract: In light of the new legal framework in force in Portugal, which defines the terms for reporting the seismic vulnerability assessment and the need for seismic strengthening of existing buildings, this paper aims at investigating the correlation between two well-known approaches for the seismic risk assessment of stone masonry buildings located within historic centres: the vulnerability index method and nonlinear static seismic analyses. The latter were carried out by using a new three-dimensional macroelement model to numerically represent the considered sample of prototype buildings, together with the application of the N2 Method. In this paper, the original purpose of the vulnerability index method, that of ranking the seismic vulnerability of existing urban cultural heritage (UCH) assets within the same building typology, was numerically validated. However, when reverting the use of the vulnerability index method by replacing the Macroseismic Intensity with a response spectrum, the results were not as interesting as envisaged, since the correlations between the vulnerability index and the main properties of the capacity curves derived from numerical models, presented, in general, a poor fitting. Finally, the possible causes for such poor fitting and future lines of investigation are discussed. Despite these results must be understood with due care and diligence, the authors believe that this exercise might encourage new investigations on this topic that could lead to the development of a new code-oriented methodology for the seismic risk assessment of UCH assets within historic centres.